T Cell Receptor-Regulated TGF-β Type I Receptor Expression Determines T Cell Quiescence and Activation - Tu, Eric; Chia, Cheryl P.Z.; Chen, Weiwei; Zhang, Dunfang; Park, Sang A.; Jin, Wenwen; Wang, Dandan; Alegre, Maria-Luisa; Zhang, Ying E.; Sun, Lingyun; Chen, WanJun (Immunity (Cambridge, Mass.), 2018)
It is unclear how quiescence is enforced in naive T cells, but activation by foreign antigens and self-antigens is allowed, despite the presence of inhibitory signals. We showed that active transforming growth factor β (TGF-β) signaling was present in naive T cells, and T cell receptor (TCR) engagement reduced TGF-β signaling during T cell activation by downregulating TGF-β type 1 receptor (TβRI) through activation of caspase recruitment domain-containing protein 11 (CARD11) and nuclear factor κB (NF-κB). TGF-β prevented TCR-mediated TβRI downregulation, but this was abrogated by interleukin-6 (IL-6). Mitigation of TCR-mediated TβRI downregulation through overexpression of TβRI in naive and activated T cells rendered T cells less responsive and suppressed autoimmunity. Naive T cells in autoimmune patients exhibited reduced TβRI expression and increased TCR-driven proliferation compared to healthy subjects. Thus, TCR-mediated regulation of TβRI-TGF-β signaling acts as a crucial criterion to determine T cell quiescence and activation. [Display omitted] •Naive T cells show active TGF-β signaling and TβR expression•Strong TCR stimulation decreases TβRI and TGF-β signaling by CARD11 and NF-κB•Overexpression of TβRI suppresses T cell response and autoimmunity•TβRI expression is reduced in naive T cells of SLE patients It is unclear how quiescence is enforced in naive T cells, yet activation is allowed. Tu et al. show that TGF-β signaling maintains T cell quiescence. Strong TCR stimuli reduce TβRI expression and consequently abolish TGF-β signaling in T cells. TCR-mediated TβRI downregulation acts as a “third criterion” to fully activate T cells in addition to the “two-signal” model.